THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE: JOB SATISFACTION AS AN INTERVENING - Sugiono, Edi; Ardhiansyah, Rizki Perdana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the influence of organizational culture on employee performance through Job Satisfaction on Employees of Digital Agencies. This study used a survey method by distributing questionnaires to the employee's PT X of Digital Agency as the respondents. This study uses Quantitative research methods, the Structural Equation Modeling (SEM) analysis technique with the application of Smart PLS version 3. Samples in this study were 110 respondents. The results showed that Organizational Culture directly had a positive and significant effect on employee performance mediated by job satisfaction. Therefore, job satisfaction is an intervening variable in this study. The variable job satisfaction can strengthen or weaken the relationship between organizational culture and employee performance.